Murder on the Ballarat train [compact disc, unabridged] : a Phryne Fisher mystery - Greenwood, Kerry (Greenwood, Kerry. Phryne Fisher mystery., 2009)
In Phryne's third adventure, Phryne is off to Ballarat for a week of fabulousness, but the sedate journey by train turns out to be far from the restful trip she was planning. What was planned as a restful country sojourn turns into the stuff of nightmares: a young girl who can't remember anything, rumors of vile white slavery and the body of an old woman missing her emerald rings. And Phryne is at the centre, working through the clues to arrive at the incredible truth.